(untitled) (International Journal of Environmental Sciences, 2025)
Pili Nuts (Canarium Ovatum), primarily found in the Province of Sorsogon in the Bicol region of the Philippines, offer a promising alternative for enhancing concrete durability while addressing sustainability and environmental concerns. The research focuses on Pili Nut Shell Powder (PNS) as a partial replacement of fine aggregate in different percentages (5%, 10%, and 15%) and evaluates the specimens at 7, 14, and 28 days. Results from durability tests, including Water Absorption (WA), Sorptivity Test (ST), and Rapid Chloride Ion Penetration Test (RCPT), underscore the positive influence of PNS on concrete properties. Notably, the 15% PNS mixture consistently outperforms, showcasing its potential to enhance concrete durability. Additional findings highlight that the 28-day water absorption of the controlled mix improved with the 15% PNS mixture, achieving a 23.3% reduction at 2.3% water absorption. In Sorptivity testing, the controlled mix displayed cumulative absorption ranging from 0.1% to 1.0% at 1 to 20 minutes. In contrast, the 15% PNS group consistently exhibited the lowest sorptivity rates, varying from 0% to 0.3% at the same intervals. For the 28-day cured specimens in the Rapid Chloride Ion Penetration Test, the controlled mix registered an average charge of 3438 coulombs. In comparison, the 15% PNS mixture proved the most effective, with the lowest average charge of 3123 coulombs, indicating enhanced resistance to chloride penetration and improved concrete durability. This research indicates an innovative approach to endorse PNS as a sustainable resource, contributing to the environmental and economic sustainability of the construction industry, with the 15% PNS mixture showing a promising result for enhancing concrete durability.